ETIKA DAN INTEGRITAS MANAJEMEN KEPEMIMPINAN BERDASARKAN NORMA PANCASILA - Devra, Desi Devrika (Komunitas Manajemen Kompetitif, 2025)
Leadership that promotes ethics and integrity is the key to success in running an organization, especially in the midst of various modern challenges such as globalization and technological change. In Indonesia, the values of Pancasila are a relevant moral guide for creating dignified and effective leadership. This article discusses the application of Pancasila in leadership, focusing on how principles such as Divinity, Humanity, Unity, Deliberation, and Social Justice can shape a leadership style that is responsible, fair, and in favor of the common good.Through analysis of various sources such as literature, organizational reports, and case studies, this research shows that Pancasila values have an important role in strengthening organizational trust, resolving conflicts fairly, and creating inclusive decision-making processes. For example, the Second Precept encourages leaders to respect human rights, while the Fourth Precept supports a collective approach in every decision taken.However, implementing these values is not without obstacles. Some of the challenges faced include a hierarchical organizational culture, lack of education on Pancasila values, and the influence of global norms that sometimes do not fit the local context. To overcome this, a strategy is needed that includes comprehensive education of Pancasila values, the establishment of a transparent work culture, and regulations that support the application of local norms in management.By making Pancasila the basis of leadership, organizations in Indonesia are not only able to better face global challenges, but also strengthen the nation's cultural values in daily leadership practices.